2022
DOI: 10.1007/s00432-022-04187-8
|View full text |Cite
|
Sign up to set email alerts
|

Looking at NSAIDs from a historical perspective and their current status in drug repurposing for cancer treatment and prevention

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are one of the most frequently prescribed drug classes with wide therapeutic applications over the centuries. Starting from the use of salicylate-containing willow leaves to the recent rise and fall of highly selective cyclooxygenase-2 (COX-2) inhibitors and the latest dual-acting anti-inflammatory molecules, they have displayed a rapid and ongoing evolution. Despite the enormous advances in the last twenty years, investigators are still in search of the design an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…In terms of its expression, COX-2 is an immediate-early gene that is rapidly and massively upregulated to meet the high demand for PGs during inflammation, and elevated COX-2 levels are hallmarks of chronic inflammation and many types of malignancies 27 . Whereas the majority of the high-volume literature concerning COX-2 focuses on its transcriptional regulation 1 and the pharmacological means to inhibit its enzymatic activity 28 , very little is known about pathways that clear COX-2 from the cell. This question is of particular importance given the rapid inactivation of COX-2 by its catalysis products.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of its expression, COX-2 is an immediate-early gene that is rapidly and massively upregulated to meet the high demand for PGs during inflammation, and elevated COX-2 levels are hallmarks of chronic inflammation and many types of malignancies 27 . Whereas the majority of the high-volume literature concerning COX-2 focuses on its transcriptional regulation 1 and the pharmacological means to inhibit its enzymatic activity 28 , very little is known about pathways that clear COX-2 from the cell. This question is of particular importance given the rapid inactivation of COX-2 by its catalysis products.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the discovery of chemotherapeutic agents has been directed toward drug repurposing, focusing on several classes of anti-inflammatory drugs [ 40 ], especially the non-steroidal anti-inflammatory drugs (NSAIDs) [ 41 ]. Crude extracts from various parts of C. siamea were reported to exhibit in vivo anti-inflammatory activity [ 38 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, earlier studies demonstrated the potential advantages of NSAIDs in reducing the likelihood of delirium and mortality [ 8 ]. Despite the significant progress made over the past two decades, researchers continue to seek methods to design and develop more effective and safer therapies for treating inflammatory conditions [ 9 ]. This quest has become particularly compelling due to recognizing inflammation as a shared underlying factor and a unifying mechanism in most chronic diseases [ 9 ].…”
Section: Introductionmentioning
confidence: 99%